Efek Pemberian Pupuk Organik Cair Berbasis Kulit Buah (Eco Enzyme) terhadap Pertumbuhan Tanaman Pakcoy (Brassica chinensis L.) - Wulan Sari Sinaga; Desyana Millenia Limeranto; Eugenia Larissa Bakti Pangala; Kukuh Madyaningrana (Pro-Life, 2023)
Household organic waste can be used as material for organic fertilizer for supporting urban farming activities. Organic fertilizer is beneficial as an effort to reduce waste’s negative impact to environment, and to minimize the use of chemical fertilizers. This research aimed to study the macro nutrient content of fruit peel based-liquid organic fertilizer (LOF) and its effect on the growth of Pakcoy (Brassica chinensis L.). Several fruit peels from household organic waste such as banana, mango, orange, dragon fruit, and papaya peels were used as material for LOF preparation. The research was conducted with completely randomized design (CRD) method with 5 treatments and 5 replications, namely the K- (without fertilizer, only water), K+ (0.2 mL commercial LOF), P1 (0.1 mL fruit peel based-LOF), P2 (0.2 mL fruit peel based-LOF) and P3 (0.4 mL fruit peel based- LOF) for 56 days of observation. The obtained data were analyzed using one-way ANOVA. Results showed that macro nutrients of fruit peel based LOF did not yet meet the quality standards set by the Ministry of Agriculture, and the dose of 0,4 ml fruit peels based-LOF showed the best effect to support the growth of the Pakcoy plant in all Pakcoy growth parameters. Keywords: Fruit Peels, eco enzyme, macro-nutrients, pakcoy